Penyuluhan Dan Praktik Perilaku Hidup Bersih Dilingkungan SD GMIT Bone Di Kecamatan Nekamese Kabupaten Kupang Dalam Mewujudkan Masyarakat Peduli Sehat - Agnes Rantesalu; Ni Ketut Yuliana Sari; Novian Yudhaswara (Sekolah Tinggi Ilmu Administrasi Yappi Makassar, 2024)
Health is a state of well-being, encompassing physical, mental, spiritual, and social aspects that enable individuals to live productively both socially and economically. Generally, in society, the understanding of clean living behaviors is still low due to a lack of information on the importance of clean living behaviors and the limited facilities that support them. Early introduction to clean living behaviors is crucial so that children become accustomed to practicing them. This community service activity is carried out to enhance the knowledge, awareness, willingness, and ability of the community, especially students of SD GMIT Bone, to engage in Clean and Healthy Living Behaviors (PHBS) and to provide facilities that enhance awareness of clean and healthy living. One way to prevent health problems is by educating children on how to wash their hands with soap and the importance of personal hygiene. The PHBS education and practice provided to children help increase their awareness of clean living behaviors and maintaining environmental cleanliness with the facilities provided.